ISLAM AND SUNDANESE CULTURE: HARMONIZING MORAL, SPIRITUAL, AND HUMANITARIAN VALUES - Emiliawati, Emil; Alfajrin, Muhammad Fakih; Sarah, Siti; Parhan, Muhamad (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2025)
Islam is an open religion in the fields of science and culture, accommodating yet selective. Islam accepts science and culture that are in line with and do not contradict Islamic principles. Various cultures and customs inherited from ancestors have developed and assimilated with Islamic teachings. Local cultural wisdom must be preserved and maintained as long as it does not conflict with Islamic law. This study aims to identify Sundanese culture that contains religious and cultural values that are worth preserving from an Islamic perspective. The culture of a region is a reflection of that region's unique characteristics. Sundanese culture is known for its strong moral, spiritual, and humanitarian values, although there are negative elements that need to be filtered out. Cultural heritage such as Wayang Golek and Gembyung contain profound Islamic teachings and are still preserved by the community as a means of drawing closer to Allah SWT. The culture and customs practiced have high educational and religious value. Key Words: Culture, Islam, Sunda, Gembyung, Wayang Golek